THE INCREASING KNOWLEDGE ABOUT PERSONAL HYGIENE IN ODGJ (PEOPLE WITH MENTAL DISORDERS) IN THE KUTOREJO DISTRICT MOJOKERTO - Ninik Murtiyani; Sudah Hartin; Auda Nur Imania; Nila Kurnia Setiawan (Community Service Journal of Indonesia, 2021)
Community Service Activities organized by the Dian Husada Nursing Academy in collaboration with Al Hidayah Kutorejo Mojokerto shelter house held health counseling with participants of all ODGJ patients (People with Mental Disorders) with the theme “Increasing Public Knowledge About Personal Hygiene in ODGJ (People With Mental Disorders)”. Health counseling will be held on Wednesday, April 14, 2021 at the Al Hidayah Kutorejo Mojokerto shelter. This activity was carried out in a team consisting of two Akper Dian Husada lecturers, 2 students, and a team from the AL Hidayah Kutorejo Mojokerto shelter. The activity was arranged by the team for two weeks, starting from determining the theme of the activity, the form of the activity, the timing of the activity, and first socializing the activity to ODGJ patients. This activity was witnessed by all patients with ODGJ (People with Mental Disorders). The form of evaluation of this community service activity that went smoothly was the enthusiasm of ODGJ patients (People with Mental Disorders) in participating in the activity by asking questions about personal hygiene to the presenter.